The microbiome’s hidden influence: preclinical insights into inflammatory responses in necrotizing enterocolitis - Briana M. Peterson; Ina Rudloff; Nadia S. Deen; Sara K. Di Simone; Ramesh M. Nataraja; Gergely Toldi; Maurizio Pacilli; Steven P. Garrick; Steven X. Cho; Marcel F. Nold; Samuel C. Forster; Claudia A. Nold-Petry (Seminars in Immunopathology, 2025)
Necrotizing enterocolitis (NEC) is the most common surgical emergency in preterm infants; nonetheless, besides supportive measures, no treatment is available. NEC significantly increases length of hospitalization of preterm infants, causes severe morbidity and up to 70% mortality. Despite limited understanding of the underlying mechanisms, prematurity, dysbiosis and an underdeveloped immune system are known to increase the risks of developing NEC. The low weight of preterm infants (often < 2000 g) and unpredictable progression of NEC hinder clinical research; hence, most of our mechanistic understanding of NEC pathophysiology has arisen from animal models. Recent advances in bacterial genomic analyses highlighted the intestinal microbiome’s key role in NEC, strengthening the concept that this disease results from an interaction between the patient’s developing immune system and their microbiome. This notion is supported by the moderate effect of probiotics in preventing NEC. Here, we review the current knowledge on how the immune system interacts with the intestinal microbiome in early life, including in relation to NEC, describe the current evidence from cohort studies, clinical trials, in vivo and in vitro models used to study NEC, and methods to modulate the immune system and microbiome in early life. Knowledge on the early-life microbiome and immune system in health and diseases, including NEC, can be harnessed to develop novel and urgently needed immunomodulatory and microbiota-based therapeutics.